[001] preferentially-oriented 2D tungsten disulfide nanosheets as anode materials for superior lithium storage1. Issue 34 (14th September 2015) - Yang, Wanfeng; Wang, Jiawei; Si, Conghui; Peng, Zhangquan; Frenzel, Jan; Eggeler, Gunther; Zhang, Zhonghua
<x xml:space="preserve">Abstract</x> Two-dimensional WS2 nanosheets with preferential [001] orientation and perfect single crystalline structures exhibit superior lithium storage performance.